Mxene surface on multiple junction triangles for determining osteosarcoma cancer biomarker by dielectrode microgap sensor - Zhou, D. (Dove Medical Press Ltd, 2020)
Background: In recent years, nanomaterials have justified their dissemination for biosensor application towards the sensitive and selective detections of clinical biomarkers at the lower levels. MXene is a two-dimensional layered transition metal, attractive for biosensing due to its chemical, physical and electrical properties along with the biocompatibility. Materials and Methods: This work was focused on diagnosing osteosarcoma (OS), a common bone cancer, on MXene-modified multiple junction triangles by dielectrode sensing. Survivin protein gene is highly correlated with OS, identified on this sensing surface. Capture DNA was immobilized on MXene by using 3-glycidoxypropyltrimethox-ysilane as an amine linker and duplexed by the target DNA sequence. Results: The limitation and sensitivity of detection were found as 1 fM with the acceptable regression co-efficient value (y=1.0037â¨° + 0.525; R2=0.978) and the current enhancement was noted when increasing the target DNA concentrations. Moreover, the control sequences of single-and triple-mismatched and noncomplementary to the target DNA sequences failed to hybridize on the capture DNA, confirming the specificity. In addition, different batches were prepared with capture probe immobilized sensing surfaces and proved the efficient reproducibility. Conclusion: This microgap device with Mxene-modified multiple junction triangles dielec-trode surface is beneficial to quantify the survivin gene at its lower level and diagnosing OS complication levels. Â© 2020 Zhou et al.